Phytochemical Screening of Ethnomedicinal Herbal Extracts and their Effect on Microbial Quality of Sukuti - Rai, Sangen Ruma (Himalayan Journal of Science and Technology, 2022)
The effect of herbal extracts of four ethnomedicinal herbs (Zanthoxylumarmatum, Litsea cubeba, Heracleum nepalense, and Evodia fraxinifolia) of culinary importance on the microbial quality of sukuti (a traditional dried meat product) was studied. Herbal extracts were prepared by grinding each herb to particle size < 250 μm, extracting in 50% (v/v) ethanol, and concentrating in a rotary vacuum evaporator at 50oC. Four of the spoilage and pathogenic microorganisms, viz., Salmonella, Staphylococcus, E. coli, and Lactobacillus were isolated from market sukuti samples and used as test organisms for the study. Herbal extracts at the concentration of 40, 20, 10, and 2 mg/ml were tested against the test organisms to determine the antimicrobial property of the extracts. The herbal extract showing the greatest antimicrobial activity was selected for use in optimized product (sukuti) development. The total phenolic content of the herbal extracts was also determined. The analyses were performed in triplicate. The data were checked for homogeneity before being analyzed with ANOVA in Genstat Release v12. The Fisher's Least Significant Difference (LSD) method was used to compare data means at a 5% level of significance. Zanthoxylum armatum at 40 mg/ml concentration showed the largest zone of inhibition (ZOI) against the test organisms and was therefore selected for final product development. Meat strips (1 cm × 1 cm × 25 cm) were marinated with Zanthoxylum armatum (40 mg/ml) extract at the rate of 2%, aged (24 h at 4 ± 2oC), and dried in a cabinet dryer for 2 days at 55oC. The total plate counts (TPCs) of control (untreated)- and herbal (treated) sukuti were carried out for 20 days at an interval of 10 days to determine the microbial stability of the final product. The TPC for the treated sample was significantly lower (p